A Survey on Marketing Potential of Maize Seed Production in the Western Hill of Nepal (Nepal Agriculture Research Journal, 2009)
A Marketing Rural Rapid Appraisal Survey (MRRA) was conducted from 12-16 June 2002 inBhakimli (1725 masl), Myagdi district. Two factors namely gender (male and female) and wealthcategory rich, medium and poor were considered in accessible area of Bhakimli. Semi-structuredquestionnaires and checklist were used to collect information on maize seed production, marketingopportunities and marketing system for producers, traders and consumers. The objectives of thestudy were to understand existing maize seed production, demand and supply; to identify theproblems associated with the seed marketing system and policy options for sustainable maize seedproduction. Farmers groups in Bhakimli were involved in maize seed production and managementof marketing. Successful seed production for long-term would ensure a continuous supply of openpollinated variety (OPV) seed in farmers' level. Seed production as a new commercial enterprisecreated employment opportunities as well as income generating in the Western hills of Nepal.Keywords: Commercial enterprises; community seed production; employment; income generating;marketing potentialDOI: 10.3126/narj.v7i0.1873Nepal Agriculture Research Journal Vol.7 2006 pp.82-87